2013
DOI: 10.1186/1471-2458-13-133
|View full text |Cite
|
Sign up to set email alerts
|

Which outcome expectancies are important in determining young adults’ intentions to use condoms with casual sexual partners?: a cross-sectional study

Abstract: BackgroundThe prevalence of unwanted pregnancy and sexually transmitted infection amongst young adults represents an important public health problem in the UK. Individuals’ attitude towards the use of condoms has been identified as an important determinant of behavioural intentions and action. The Theory of Planned Behaviour has been widely used to explain and predict health behaviour. This posits that the degree to which an individual positively or negatively values a behaviour (termed ‘direct attitude’) is b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 40 publications
(54 reference statements)
1
22
0
2
Order By: Relevance
“…Additionally, studies have found negative outcome expectancies associated with lower intentions to use condoms (Newby et al, 2013) and less condom use (Albarracín et al, 2000), and safe sex outcome expectancies did not predict condom use (Albarracín et al, 2000). This indicates that the scale developed and analyzed in the current study assesses similar aspects of condom use expectancies, while it is more comprehensive for this specific, high-risk population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, studies have found negative outcome expectancies associated with lower intentions to use condoms (Newby et al, 2013) and less condom use (Albarracín et al, 2000), and safe sex outcome expectancies did not predict condom use (Albarracín et al, 2000). This indicates that the scale developed and analyzed in the current study assesses similar aspects of condom use expectancies, while it is more comprehensive for this specific, high-risk population.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with the research findings reported here. Finally, similar to our approach, Newby and colleagues (2013) reviewed research that elicited condom use expectancies and combined the most commonly elicited responses to develop and test a scale. They also found an association between condom use expectancies and intentions to use condoms (Newby et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Es de naturaleza aprendida (Ajzen & Fishbein, 1975) y constituye un factor determinante para que la conducta finalmente se lleve a cabo (Newby, Brown, French, & Wallace, 2013 las actitudes positivas hacia el uso del preservativo inciden en su uso habitual (e.g., Castro, Bermúdez, Buela-Casal, & Madrid, 2011;Giménez-García, Ballester-Arnal, Gil-Llario, Cárdenas-López, & Durán Baca, 2013). Además, las actitudes de los adolescentes sobre la sexualidad están muy influenciadas por las actitudes que existen en el seno familiar (Ferreira et al, 2013).…”
Section: Introductionunclassified